Correction of the convicts as the purpose of criminal and criminal-executive law - Shevtsov, Yuri (Journal of the Belarusian State University. Law, 2019)
The article deals with the concept of correction of convicts as the purpose of criminal responsibility. A comparative analysis of the consolidation of this purpose in the criminal law of Belarus, Kazakhstan, the Russian Federation and Ukraine is carried out. Various scientific approaches are analyzed in the understanding of the purpose of correcting in the doctrine of criminal and penitentiary law. The content of the correction is considered in moral and legal aspects. The article proves the necessity of a differential approach and consideration of specifics in considering the purpose of «correction» in criminal and penitentiary law, and regard to punishment related to isolation from society and other measures of criminal responsibility and punishment without isolation from society.